ANALISIS PENGARUH INFLASI DAN KURS TERHADAP INDEKS SAHAM SYARIAH INDONESIA (ISSI) TAHUN 2014-2018 - Syaiful Anwar; Adni Dwi A (I-Finance Journal, 2020)
This study aims to find out empirically the effect of inflation and exchange rates on the movements of the Indonesian Islamic Stock Index (ISSI). This research uses quantitative research methods, using multiple linear regression analysis models. Data collection uses secondary data from documentation related data. Data is taken from the monthly closing price of each variable from 2014-2018 (60 months). The research test uses the t test and F test and is processed using SPSS16. The results showed that inflation had a significant effect and the exchange rate had no partial effect on ISSI movements, but both variables had a significant simultaneous effect on the ISSI